Planning of Crop Irrigation with Treated Wastewater Using Geographic Information System - The Case of Sana’a Wastewater Treatment Plant - Gawaher, Al-Mahnash (2004)
There is water scarcity problem in arid and semiarid areas like the Sana’a basin, eventhough the cities produce a large amount of wastewater. Therefore, reuse of treated wastewater in irrigation is warranted. However, the sewerage system covers only 20 percent of the city of Sana’a. The flow to the Sana’a Wastewater Treatment Plant (WWTP) is estimated to be 50,000 m3/day by the year 2005. This is the available amount for irrigation use.